2021
DOI: 10.1002/mame.202100073
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia/Temperature/pH Triple Stimuli–Responsive Block Copolymers: Synthesis, Self‐Assembly, and Controlled Drug Release

Abstract: The amphiphilic block copolymer poly(methacrylic acid-co-2-nitroimidazole acrylate)-b-poly(2-(N,N-dimethylamino)ethyl methacrylate) (P(MAA-co-NIMA)-b-PDMAEMA) with the hypoxia/temperature/pH triple responsiveness is synthesized by reversible addition-fragmentation chain transfer polymerization (RAFT), hydrolysis, and 3-(3-dimethylaminopropyl)-1-ethylcarbodiimide (EDC) reactions, and successfully self-assembled into micelles. The hypoxia response in vitro is realized, and then the sensitivity of the self-assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In summary, the present study provides an innovative strategy to efficiently generate ROS and consume ROS scavenging system through a cascade reaction, and rationally design a highly efficient nanocatalator for tumor catalytic therapy. A large number of triple stimulus-responsive nanodrug delivery systems have been reported for tumor treatment in the TME, showing superior specificity, targeting, controllability and safety [33], for example, pH/redox/NIR triple-responsive ZnO quantum dots-conjugated hollow mesoporous carbon nanoplatform [110], light and dual-redox triple-responsive core-crosslinked micelles [111], hypoxia/temperature/pH triple-responsive block copolymers [112], and so forth. Recently, Wu et al reported a pH/thermal/glutathione triple-responsive smart supramolecular nanomedicine (FUS/ICG@PEDD) which was constructed by utilizing particular and kinetic hydrogen bonding interactions [112].…”
Section: Dual and Multiple Stimuli Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the present study provides an innovative strategy to efficiently generate ROS and consume ROS scavenging system through a cascade reaction, and rationally design a highly efficient nanocatalator for tumor catalytic therapy. A large number of triple stimulus-responsive nanodrug delivery systems have been reported for tumor treatment in the TME, showing superior specificity, targeting, controllability and safety [33], for example, pH/redox/NIR triple-responsive ZnO quantum dots-conjugated hollow mesoporous carbon nanoplatform [110], light and dual-redox triple-responsive core-crosslinked micelles [111], hypoxia/temperature/pH triple-responsive block copolymers [112], and so forth. Recently, Wu et al reported a pH/thermal/glutathione triple-responsive smart supramolecular nanomedicine (FUS/ICG@PEDD) which was constructed by utilizing particular and kinetic hydrogen bonding interactions [112].…”
Section: Dual and Multiple Stimuli Responsivenessmentioning
confidence: 99%
“…A large number of triple stimulus-responsive nanodrug delivery systems have been reported for tumor treatment in the TME, showing superior specificity, targeting, controllability and safety [33], for example, pH/redox/NIR triple-responsive ZnO quantum dots-conjugated hollow mesoporous carbon nanoplatform [110], light and dual-redox triple-responsive core-crosslinked micelles [111], hypoxia/temperature/pH triple-responsive block copolymers [112], and so forth. Recently, Wu et al reported a pH/thermal/glutathione triple-responsive smart supramolecular nanomedicine (FUS/ICG@PEDD) which was constructed by utilizing particular and kinetic hydrogen bonding interactions [112]. The supramolecular polymeric micelles were co-loaded with α, ω-functionalized symmetric hydrogen bonding precursor drug 5-fluorouracil acetate -SS-5-fluorouracil acetate (FUS) and dual photothermal/photodynamic agent (indocyanine green, ICG).…”
Section: Dual and Multiple Stimuli Responsivenessmentioning
confidence: 99%
“…Stimuli-responsive materials known as "smart" materials, have attracted great interest due to their unique properties which made them useful in many applications. [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulus-responsive drug delivery system (DDS) is a functional nanocarrier that can release drugs rapidly or at a certain rate aer entering the body by changing the structure and conguration of the carrier under the stimulation of a specic environment including light, heat, ultrasound, enzyme, and pH changes. [12][13][14][15][16][17][18] Especially, enzyme-responsive nanocarriers have been investigated extensively due to their high sensitivity, catalytic activity, and mild reaction. [19][20][21][22][23][24] As we all know, abnormal expression of enzymes is one of the markers of the occurrence and development of tumors.…”
Section: Introductionmentioning
confidence: 99%